A Case of Diffuse Pneumocephalus With Air Bubble Sign - Magar, Birat Thapa; Malik, Mubashir; Butt, Rizwan Masood; Sheikh, Faiq (Eastern Green Neurosurgery, 2020)
Background: Pneumocephalus is defined as presence of intracranial gas. It can be at any site in the cranium; isolated or at different sites simultaneously. Quantity of gas along with extent of mass effect caused by it & severity of clinical symptoms will determine the modality of treatment; i.e. conservative or surgical. Among many etiologies trauma is one, which is one of the most common cause as in our case. Multiple foci of gas scattered within the subarachnoid space, especially in the cisterns seen on CT scan of brain has been described as “Air bubble sign”, indicating of subdural tension PNC. Here we have presented our case with review of management of such condition, especially conservative. Case: A case of 55yrs male with history of road traffic accident was referred from another hospital. CT scan of Brain done in previous center showed diffuse PNC scattered throughout the subarachnoid space. The patient was managed conservatively and successive repeat CT scan showed gradual to complete resorption of gas and simultaneous clinical improvement of the patient. Conclusion: “Air bubble sign” described as a sign of tension PNC can be managed conservatively in absence of significant clinical symptoms and may not only be associated with subdural tension PNC. The modality of treatment of PNC as well for tension PNC should be tailored according to the patient’s clinical status.